The Old and the New on Viral Diseases in Sturgeon - Davide Mugetti; Paolo Pastorino; Vasco Menconi; Claudio Pedron; Marino Prearo (Pathogens, 2020)
Although sturgeon production by aquaculture has increased worldwide, a major factor limiting its expansion are infectious diseases, although few data about viral diseases are available however. This review provides a rapid overview of viral agents detected and described to date. Following a general introduction on viral diseases are four sections arranged by virus classification: sturgeon nucleocytoplasmic large DNA viruses, herpesviruses, white sturgeon adenovirus 1, and other viruses. Molecular diagnosis is currently the best tool to detect viral diseases, since cell culture isolation is not yet applicable for the detection of most sturgeon viruses.